Hostage negotiator resilience: A phenomenological study of awe - Thompson, Jeff; Jensen, Elizabeth (Frontiers in Psychology, 2023)
Law enforcement crisis and hostage negotiators (CHNs) are tasked with resolving incidents that are stressful, unpredictable, and often dangerous. These negotiators must work as a team and be able to successfully utilize a variety of skills in order to gain the subject’s voluntary compliance and peaceful surrender. It is necessary for negotiators to continually practice these skills while also, and importantly, care for their own wellbeing. This study examines how a phenomenon, awe, when viewed as a resilience practice, can support law enforcement crisis hostage negotiators with their crisis work and personal wellness. Utilizing phenomenological methodologies, the findings demonstrate that reflecting on awe experiences had an overall positive impact on the negotiators in both their professional and personal lives. Based on the results, it is suggested that awe practices could be incorporated into future negotiator trainings in order to increase resilience and assist negotiators personally and professionally.